Safety and Efficacy of Combining Biologic with Nonbiologic Therapies for Moderate to Severe Psoriasis: A Review. Issue 4 (December 2014) - Patel, Viraat; Levin, Ethan; Sorenson, Eric; Malakouti, Mona; Koo, John Y.M.
Background: Some psoriasis patients respond inadequately to monotherapy and require combination therapy. Combining a biologic and nonbiologic agent may provide improvement. Objective: To review the efficacy and safety of combination treatment with biologic and nonbiologic agents in the treatment of moderate to severe plaque psoriasis. Methods: We searched Pubmed for English-language publications evaluating combination treatment with biologic and nonbiologic therapies through June 2014. Results: Etancercept was the most commonly used biologic followed by ustekinumab, adalimumab, and infliximab. The majority of nonbiologic therapies reported were narrowband UVB (NBUVB) and methotrexate. Most cases reported increased efficacy with combination therapy with serious adverse events occurring in less than 3% of patients. Conclusion: Combination biologic plus nonbiologic therapy, especially NBUVB with biologics is a viable clinical strategy in the treatment of psoriasis patients unresponsive to monotherapy, despite limitations in the data available. However, the long-term impact of these combinations has yet to be determined.